Continuous limits of tilting modules - Braga, C.A. (Algebra and Discrete Mathematics, 2019)
We provided a constructive argument to obtain an infinite generated tilting module from a family of tilting modules satisfying some hypotheses. We also applied the result over a hereditary algebra to get the Lukas tilting module.